Enhancing Oil Recovery through Waterflooding - Grema, A. S.; Mahlon, M. K.; Kolo, A. S.; Taura, U. H. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Waterflooding is a simple and cheaper means of improving oil recovery from a reservoir by injecting water into the reservoir. Economic considerations suggest injection and production wells must be optimally placed considering reservoir geology, fluid properties, and well orientation. This study focuses on the effects of well placement and orientation on the performance of waterflooding process. The reservoir has a dimension of 2500 ft by 2500 ft by 150 ft. It is homogenous in porosity and heterogeneous in permeability. The performances of three cases considered in the study were evaluated and compared. Water production rates, bottom hole pressure limits for producer wells, well water cut and net present value (NPV) over the entire production period were considered in evaluating their performances. Reservoir modeling and simulation were carried out using MATLAB Reservoir Simulation Toolbox (MRST). It was verified from the investigation that Case III has a maximal production rate of 1,110,188.6 stb/day (stock tank barrel per day), decreasing to 11,005 stb/day after a span of 1400 days with a pressure decrease. Consequently, it was considered a better choice in terms of well placement. It was also estimated to have a maximal Net Present Value of 19.8 billion dollars, which makes it economically viable.